Presurgical cognitive status in patients with low‐grade glioma and epilepsy: Testing the effects of seizures, antiseizure medications, and tumor localization - Ilaria Guarracino; Giada Pauletto; Tamara Ius; Francesca Palese; Miran Skrap; Barbara Tomasino (Brain and Behavior, 2022)
Abstract Background Low‐grade gliomas (LGGs) are frequently associated with epilepsy. There are few studies addressing the impact of seizures, antiseizure medications (ASMs), and lesion localization on presurgery cognitive functioning. Methods We tested the relation between the above‐mentioned variables in a continuous series of 73 young patients (mean age 38.3 years ± 11.7) affected by LGGs and epilepsy. The anatomical areas, involved in this sample, were the left insula with surrounding cortical and subcortical areas, the right precentral gyrus/rolandic operculum, and the white matter and cortical regions beneath. Results Patients’ presurgery cognitive status was within the normal range, with borderline performance for some tasks. We tested whether lower scores were related with lesion or with epilepsy‐related factors. Multiple regression identified variables that predict test scores. The Token test score was predicted by a model (p = .0078) containing the DT2T1 MRI, corrected for seizure features. Object naming performance was predicted by a model (p = .0113) containing the localization, the DT2T1 MRI, corrected for sex, EEG, and onset. Verbal fluency score was predicted by a model (p = .0056) containing the localization and the DT2T1 MRI, corrected for AEDs and EEG. Working memory score was predicted by a model (p = .0117) containing Engel class, the DT2T1 MRI, corrected for sex. Clock drawing score was predicted by a model (p < .0001) containing the Engel class, AEDs, and EEG. TMT A score was predicted by a model (p = .0022) containing localization, corrected for EEG. TMT B‐A score was predicted by a model (p = .0373) containing localization. Voxel Lesion Symptom Mapping analyses carried out on patients’ lesion volumes confirmed that patients’ level of performance correlated with lesion‐related variables. Conclusion This preliminary study indicates that the presurgical level of performance for language tasks and for cognitive flexibility and shifting is mainly predicted by lesion‐related variables, working memory by both lesion and epilepsy‐related variables. Epilepsy clinical and instrumental characteristics predicted performance for visuospatial planning.